A Novel AGEI Solution of Parabolic Equation for EM Scattering Problems - Shifei Tao , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Parabolic equation (PE) has been widely used for EM propagating and scattering problems for its high efficiency. By using the finite differential (FD) method, the calculation can be taken in a series of transverse planes in a marching manner. In this paper, the alternating group explicit iterative (AGEI) method is applied to solve the alternating direction implicit based parabolic equation (ADI-PE). As a result, the CPU time can be further saved when compared with the CN-PE and ADI-PE methods. Numerical results are shown for demonstrating the accuracy and efficiency.